Kako institucije pričaju priče: zločin u franjevačkom samostanu u Bosni - Čaušević, Ekrem (2013)
In 1855, outside the Franciscan Monastery at Plehan, near Dervanta, in North Bosnia, a Muslim man was murdered and his corpse burned. Several friars and local villagers were accused of the murder and imprisoned by the Ottoman Bosnian authorities. On the basis of letters written by the Franciscans who were directly or indirectly involved in the incident, and some additional sources, the authors of this paper approach the case with the aim of understanding the way in which the members of a community, in this instance the local Franciscan community, developed and applied specific thought styles, how they differentiated themselves from their Others (Muslims and Orthodox Christians), and how they consequently interpreted the conflict situation which led to the murder, persistently absolving themselves of any guilt.
Projekt MZOS
HRV